An evaluation of aerodynamics performance of a moving car with wind turbine system - Jamit, Rexca (2014)
This study presents a simulation result of an evaluation of the aerodynamic performance of a moving car with a wind turbine system. Sedan type cars (approaching the size of Proton Wira car) were modeled using the SolidWork software and simulation was done by ANSYS FLUENT software. Three car models with different wind turbine system positions (in front of the front bumper, on top of the hood and on top of the roof) plus one model without the wind turbine system were simulated. The study proved that the position of the wind turbine system installation will change the characteristic of the air flow around the car body and affects the aerodynamic performance of the car. Extended front bumper of a car is not significantly affecting the aerodynamics performance of the car. This extended bumper seems to be the suitable area to install a wind turbine system and the investigation shows that the aerodynamics performance of the car improved due to the lower drag coefficient, Cd. Optimum power generation will be based upon the amount of air velocity the duct system create in order to rotate the blades.